STRATEGI PENGEMBANGAN AGRIBISNIS KOMODITAS PADI DI KABUPATEN KARAWANG PASCA PANDEMI COVID-19 - Dinda Sahara; Abubakar Abubakar; Luthfi Nur'azkiya (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The Karawang Regency is one of the rice barns in West Java. Apart from having an agricultural area of 94,231 hectares, this district also contributes to the rice produced by the Province of West Java. Since 2018, the harvested area and yield of rice production in Karawang Regency have decreased, followed by a decrease in raw rice fields every year. Plus, the Covid-19 pandemic, which we do not know when it will end, has the potential to disrupt the availability and supply chain of food in Karawang Regency. The problem becomes more complex when farmers' institutions are still not strong, especially in terms of management, financial management, market access, and the low income of farm workers. Therefore, a strategy is needed to develop agribusiness, especially for rice commodities in Karawang Regency after the Covid-19 pandemic. This study aims to analyze the strengths, weaknesses, opportunities and threats in developing rice commodity agribusiness, formulate alternative strategies, and determine strategic priorities that the Karawang Regency government should choose to develop rice commodities in an effort to improve food security after the Covid-19 pandemic. The type of research used is descriptive research with quantitative and qualitative approaches. The location of the research was chosen purposively, namely Tempuran, Rawamerta and Pangkalan districts. The number of samples taken was as many as 16. The results showed that the impact of the Covid-19 pandemic was seen in the rice commodity agribusiness subsystem in Karawang Regency. The most influential was the supporting agribusiness subsystem, especially in the field of extension. QSPM analysis shows that the priority strategy that can be chosen is the optimization of government programs in increasing production with a total score of 6,251. Government programs that need to be optimized include intensification, which includes three farming businesses, and the use of agricultural technology.